(untitled) (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2025)
Brings us closer to understanding the essence of distance learning, which is one of the methods of learning based on the use of new pedagogical information and telecommunication technologies. It is theoretical and practical issues of distance learning, which is a synthetic integral and humanistic form of education, that should solve a large part of the problems facing the national education system in the context of educational reform.